Ultrasound-guided fine needle aspiration thyroglobulin in the diagnosis of lymph node metastasis of differentiated papillary thyroid carcinoma and its influencing factors - Su, Xuejiao; Shang, Lei; Yue, Can; Ma, Buyun (Frontiers in Endocrinology, 2024)
Background :Ultrasound-guided fine needle aspiration thyroglobulin (FNA-Tg)is recommended for the diagnosis of lymph node metastasis (LNM)in differentiated thyroid cancer(DTC), but its optimal cutoff value remains controversial, and the effect of potential influencing factors on FNA-Tg levels is unclear.Method: In this study, a retrospective analysis was conducted on 281 patients diagnosed with DTC, encompassing 333 lymph nodes. We analyze the optimal cutoff value and diagnostic efficacy of FNA-Tg, while also evaluating the potential influence of various factors on FNA-Tg.Results：For FNA-Tg, the optimal cutoff value was 16.1 ng/mL (area under the curve(AUC)= 0.942). The optimal cutoff value for FNA-Tg/sTg was 1.42 (AUC = 0.933). The AUC for FNA combined with FNA-Tg yielded the highest value compared to other combined diagnostic methods (AUC = 0.955). It has been found that serum thyroglobulin (sTg) is positively correlated with FNA-Tg (Rs = 0.318), while serum thyroglobulin antibodies (sTgAb) is negatively correlated with FNA-Tg (Rs = -0.147). In cases where the TNM stage indicated N1b, the presence of large or high volume lymph node metastasis(HVLNM), lymph node lateralization/suspicion (L/S) ratio≤2, ultrasound findings indicating lymph node liquefaction, calcification, and increased blood flow, patients with coexisting Hashimoto's thyroiditis(HT), a tumor size ≥10 mm, and postoperative pathology confirming invasion of the thyroid capsule, higher levels of FNA-Tg were observed. However，the subgroup classification of DTC and the presence or absence of thyroid tissue did not demonstrate any significant impact on the levels of FNA-Tg. Conclusion: The findings of this study indicate that the utilization of FNA in conjunction with FNA-Tg is a crucial approach for detecting LNM in DTC. TNM stage indicated N1b， the presence of HVLNM ，the